Lexicalization of pulling and pushing events in polish and english - Lozinska, Joanna; Hendriks, Henriette (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines and compares the lexicalization patterns of pulling and pushing events in two satellite-framed languages: Polish and English. On the basis of the descriptions of pulling and pushing events in two novels and their translations from Polish into English and English into Polish, four main differences between the lexicalisation of caused motion in Polish and English were found. First, with regards to our token analysis, Polish data includes more manner verbs (e.g. pchać ‘push’ and ciągnąć ‘pull’) than English. English, instead, uses generic verbs (such as put, get, take, remove). In this respect patterns of caused motion expression appear to be similar to those described for voluntary motion in previous literature. Second, and in terms of types, however, Polish and English data included similar number of motion verbs. Third, the obligatory use of perfectivizing prefixes in Polish necessitates the expression of Path, which is less frequent in the English data. Finally, our analysis also points to a higher frequency of pulling events when compared with pushing events for both languages, which is explained by the object’s becoming available to the agent as a result of this action. The present study contributes to the understanding of the expression of caused motion in the category of satellite-languages and points to the influence of morpho-syntactic characteristics of a given language on the sematic content of the descriptions of motion events.